RELEVANSI DAN IMPLEMENTASI SIKAP SISWA KELAS BAHASA ARAB DI MTS AL-MAHRUSIYAH TERHADAP KARAKTERISTIK SOSIAL SETIAP INDIVIDU - Fitriyah, Immaa Iyyaanal; Maziyyatul Muslimah (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
Adolescence is a time filled with turmoil that affects his social character. In this case, the social nature of adolescents is classified into two based on their communication patterns. The social characters are introverts and extroverts. This research was conducted to determine the character of class VIII MTs teenagers. Al-Mahrusiyah Lirboyo Kediri City. This type of research is field research that focuses on explaining the data in detail with supporting scientific reasons. The analysis technique used in this research is the descriptive analysis technique. The result of this study is that the ratio between introverted and extroverted characters is more extroverted than the last, so the role of parents and teachers in developing adolescent characters is very much needed in assisting the growth and cultivation of character education.